Conscientiousness on Affective Commitment to Change: The Mediating Role of Psychological Ownership - M Halim; Rodhiah Umaroh; Nur Halimah Siahaan; Aldini Nofta Martini; Risya Khaerun Nisa (Hasanuddin Economics and Business Review, 2024)
Based on self-determination theory, this study identified the effect of conscientiousness on the affective commitment to change of lecturers in Indonesian universities. This study empirically examined the uniqueness of conscientiousness which is strongest and most consistently associated with various outcomes. The mediation effect of psychological ownership of lecturers was also examined. A total of 321 responses were analyzed using a two-stage structural equation modeling (SEM) approach to confirm factors and test the study hypotheses. The results showed that the level of conscientiousness had a significant effect on psychological ownership. Conscientiousness had a significant indirect effect on affective commitment to change only through the psychological ownership of the lecturers. These results support the mediating role of lecturers' psychological ownership level in explaining the influence between conscientiousness and the level of affective commitment to change for lecturers.